Political Intervention in Indonesian Legislation - Muhammad Satria; Munajah Munajah; Sulistia Ningsih Rahayu; Suryadi Suryadi (Faculty of Law, University of Mataram, 2019)
The purpose of this research discusses political intervention in legislation in Indonesia to examine the problems that occur in the process of making laws. Based on the problems examined by the author, the research method used is a normative research method. Normative legal research methods or library research methods are methods or methods used in legal research conducted by examining existing library materials. Law intervention results in the form of ratification of the agenda of the intervention, and the Articles then become the basis for activities that are detrimental to the people at large and are contrary to ideology, religion for the Indonesian people. Thus, the intervention of the Law harms the nation extensively.